Pengaruh Cedera Otak Kecil (Cerebellum) terhadap Perkembangan Bahasa Anak - Gulbi, Hidayani Asi Saripa; Anggraini, Nandeea Dwi; Sari, Diyah Permata (TSAQOFAH, 2024)
The aim of this research is to understand the impact of cerebellar injury on children's language development. This study uses a library research approach. The findings indicate that injuries to the cerebellum have the potential to disrupt language development in children. The cerebellum, although small in size, plays a crucial role in coordinating movements and cognitive processes, including language. The effects of cerebellar injury include difficulties in articulation, disruptions in speech fluency, challenges in language comprehension and expression, and impairments in non-verbal communication. These issues arise due to disruptions in the fine motor coordination of the muscles needed for proper speech and language expression. The importance of appropriate intervention and treatment, such as physical therapy, speech therapy, and special educational approaches, is highlighted to help children overcome these difficulties and support their language development. In conclusion, a deeper understanding of the relationship between cerebellar injury and children's language development can aid in providing more effective interventions to improve outcomes for children affected by cerebellar injuries.